Anmeldelser - Hauge, Peter (Danish Yearbook of Musicology, 2006)
Review of: Mogens Pedersøn (Magno Petreo) ‘Madrigali e madrigaletti’, ed. Kitti Messina. Brepols: Turnhout, 2005. ‘Monumenta Musica Europea. Renaissance’, section II vol. 2.